Skills for the future health workforce Preparing health professionals for people-centred care - Maeda, Akiko (OECD Health Working Papers, 2021)
The landscape of health services delivery is undergoing significant transformation from fragmented and disease-centred toward integrated and people-centred care. Health workers find themselves at the centre of this transformation that demands from them commensurate changes in the skill-set employed in day-to-day practice, among other challenges. The paper identifies transversal (core) skills that are becoming increasingly crucial for all front-line health workers to reap the potential benefits of people-centred care, such as better patient and population outcomes, higher productivity, and higher retention/job satisfaction combined among the workers themselves. These transversal skills include interpersonal skills, such as person-centred communication, interprofessional teamwork, self-awareness and socio-cultural sensitivity, as well as analytical skills, such as adaptive problem solving to devise customised care for individual persons, system thinking, openness to continuous learning, and the ability to use digital technologies effectively. Recognising the need to prepare health professionals for meeting the dual challenges of technically and emotionally complex healthcare workplace is a prerequisite to building and maintaining resilient and resourceful health workforce. This paper provides also a brief overview of skills assessment methods and tools that could be used to evaluate the effectiveness of health workforce policies and suggests a skills assessment strategy to evaluate the impact of reforms on the skills and performance of health workforce